Periodontal bacteria influence systemic diseases through the gut microbiota - Xi, Mengying; Ruan, Qijun; Zhong, Sulan; Li, Jiatong; Qi, Weijuan; Xie, Congman; Wang, Xiaoyan (Frontiers in Cellular and Infection Microbiology, 2024)
Many systemic diseases, including Alzheimer disease (AD), diabetes mellitus (DM) and cardiovascular disease, are associated with microbiota dysbiosis. The oral and intestinal microbiota are directly connected anatomically, and communicate with each other through the oral-gut microbiome axis to establish and maintain host microbial homeostasis. In addition to directly, periodontal bacteria may also be indirectly involved in the regulation of systemic health and disease through the disturbed gut. This paper provides evidence for the role of periodontal bacteria in systemic diseases via the oral-gut axis and the far-reaching implications of maintaining periodontal health in reducing the risk of many intestinal and parenteral diseases. This may provide insight into the underlying pathogenesis of many systemic diseases and the search for new preventive and therapeutic strategies.